1997
DOI: 10.1172/jci119715
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones block tumor necrosis factor-alpha-induced inhibition of insulin signaling.

Abstract: TNF-␣ has been shown to be an important mediator of insulin resistance linked to obesity. This cytokine induces insulin resistance, at least in part, through inhibition of the tyrosine kinase activity of the insulin receptor. Recently, a new class of compounds, the antidiabetic thiazolidinediones (TZDs), has been shown to improve insulin resistance in obesity and non-insulin-dependent diabetes mellitus in both rodents and man. Here we show that TZDs have powerful effects on the ability of TNF-␣ to alter the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
3
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(166 citation statements)
references
References 50 publications
9
150
3
4
Order By: Relevance
“…They support the concept that troglitazone (PPAR␥ agonists) improves insulin responsiveness via binding to PPAR␥ receptors in the adipocyte where these receptors are expressed most prominently (6) and promotes storage of free fatty acids in adipocyte triglycerides (7,8). However, the improvement in glucose metabolism could also include altered expression of adipocyte derived mediators of insulin resistance (12)(13)(14) and, as recently proposed, repartitioning of lipids away from muscle into adipose tissue (5,11). The latter concept would be of special importance due to nuclear magnetic resonance findings showing increased intramyocellular triglyceride in insulin-resistant offspring of type 2 diabetic patients (51), although it remains to be demonstrated whether this is a primary or secondary phenomenon.…”
Section: Glycogen Synthase Activities Troglitazone Treatment Did Not mentioning
confidence: 58%
See 1 more Smart Citation
“…They support the concept that troglitazone (PPAR␥ agonists) improves insulin responsiveness via binding to PPAR␥ receptors in the adipocyte where these receptors are expressed most prominently (6) and promotes storage of free fatty acids in adipocyte triglycerides (7,8). However, the improvement in glucose metabolism could also include altered expression of adipocyte derived mediators of insulin resistance (12)(13)(14) and, as recently proposed, repartitioning of lipids away from muscle into adipose tissue (5,11). The latter concept would be of special importance due to nuclear magnetic resonance findings showing increased intramyocellular triglyceride in insulin-resistant offspring of type 2 diabetic patients (51), although it remains to be demonstrated whether this is a primary or secondary phenomenon.…”
Section: Glycogen Synthase Activities Troglitazone Treatment Did Not mentioning
confidence: 58%
“…PPAR␥ is mainly expressed in adipose tissue and, to a lesser extent, in muscle (6). The effects of PPAR␥ agonists on insulin sensitivity in skeletal muscle could therefore be indirect, involving adipose tissue PPAR␥ stimulation and leading to reductions in circulating and intramyocellular lipid levels (7)(8)(9)(10)(11) or alterations in the secretion of factors that modulate skeletal muscle insulin action (12)(13)(14). Alternatively, PPAR␥ agonists exhibit local (direct) intramyocellular actions, as suggested in some studies (10,15,16), although it remains to be investigated whether PPAR␥ agonists regulate gene expression in muscle by direct receptor activation.…”
mentioning
confidence: 99%
“…28 Furthermore, numerous animal models of obesity and insulin resistance based on spontaneous genetic mutations or experimentally created gene deletions have been investigated to clarify the molecular mechanisms and role of different signal pathways and molecules involved in the development of these diseases. 29 -31 Also in these models it has been shown that TNF-a negatively interferes with insulin receptor signaling, 32,33 while, on the other hand, obese mice with a targeted null mutation in the gene encoding TNFa and those encoding the two receptors for TNFa showed a significant improved insulin sensitivity. 34 These mice had lower levels of circulating FFA, and were protected from the obesity-related reduction in the insulin receptor signaling in muscle and fat tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For experimental purposes, Kupffer cells were used on the 3rd day of culture. t-RA (Sigma, St. Louis, MO), 9-cis RA (Sigma), an RAR-selective agonist Ro13-7410 (F. Hoffmann-LaRoche, Ltd., Basel, Switzerland), 5 an RAR-selective antagonist Ro41-5253 (F. Hoffmann-LaRoche, Ltd.), 5 an RXR-selective agonist Ro47-5944 (F. Hoffmann-LaRoche, Ltd.), 19 a PPAR-␥-selective agonist AD4833 (pioglitazone hydrochloride, Takeda, Ltd., Osaka, Japan), 20 and a RXR-selective agonist LG268 (Ligand Pharmaceuticals, La Jolla, CA) 21 were each dissolved in dimethyl sulfoxide and applied to the Kupffer cells at a volume of less than 0.5% of the volume of the medium. In the control condition of each experiment, the medium was supplemented with 0.5% DMSO to examine the possible effects of DMSO on the cells, and we confirmed that 0.5% DMSO does not affect the LPS-induced production of TNF-␣ and NO in Kupffer cells.…”
Section: Methodsmentioning
confidence: 99%